Bioassay-guided isolation of antioxidant, antibacterial, and antidiabetic compounds from Aleuritopteris bicolor of Nepal: In vitro/in silico study - Rekha Bhandari; Sadikshya Sapkota; Peru Kumari Bishwakarma; Shailendra Kumar Sharma; Ram Kishor Yadav; Sandesh Poudel; Siddha Raj Upadhyaya; Ganga Ram Upadhayay; Sajan L. Shyaula; Khem Raj Joshi (PLoS ONE, 2026)
Aleuritopteris bicolor , a fern species known locally as “Raani Sinkaa” in Nepal, has traditionally been used to treat wounds, diarrhea, dysentery, and gastritis. Despite its widespread use, scientific data on its bioactive compounds and bioactivities remain limited. To address this gap, this study aimed to isolate bioactive compounds from A. bicolor and evaluate their antioxidant, antibacterial, and antidiabetic properties using both in vitro and in silico methods. The 70% methanol extract of A. bicolor afforded three compounds: 20-hydroxyecdysone ( 1 ), and a mixture of quercetin 3- O - β -D-glucopyranoside ( 2 ) and quercetin 3- O - β -D-galactopyranoside ( 3 ), isolated via column chromatography. The structures of the isolated compounds were elucidated based on spectroscopic (NMR) and spectrometric (LC-MS) analyses. Compound 1 exhibited weak antioxidant activity, with an IC 50 of 38.38 ± 3.41 µg/mL in the DPPH free radical scavenging assay. In contrast, the mixture of compounds 2 and 3 demonstrated significant antioxidant activity, with an IC 50 of 1.56 ± 0.3 µg/mL, surpassing the standard ascorbic acid (IC 50 : 4.15 ± 0.3 µg/mL). Compounds 2 and 3 also showed moderate antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae . Furthermore, these compounds exhibited notable inhibition of α -amylase and α -glucosidase enzymes in in vitro assays, with EC 50 values of 99.48 ± 3.2 µg/mL and 68.53 ± 1.7 µg/mL, respectively. In silico molecular docking analyses supported these enzyme inhibitions by revealing favorable interactions between compound 2 and key catalytic residues of the target enzymes, with binding energies of −7.2 kcal/mol for α -amylase and −7.1 kcal/mol for α -glucosidase. Additionally, ADMET analysis suggests further lead optimization of compounds 2 and 3 . This study successfully isolated three bioactive compounds from A. bicolor and recommends further medicinal chemistry and in vivo investigations to establish their therapeutic potential as antidiabetic phytomedicine.